Skin Cancer Preventive Behaviors and Its Determinants among High School Students in Sanandaj, Iran: An Application of PRECEDE Model - Athareh Najafi; Elahe Nadrian; Gona Bakri; Haidar Nadrian; Asaad Fathipour (Hamadan University of Medical Sciences, 2017)
Background and Objectives: The prevalence of skin cancer has been rising in Iran in the recent years. This disease is the most common cancer in Kurdistan province, Iran. Regarding this, the present study aimed to investigate the determinants of skin cancer preventive behaviors (SCPBs) among the high school students of Sanandaj, Iran, using the PRECEDE model. Materials and Methods: This descriptive cross-sectional study was conducted on 225 second- and third-grade high school students (age range: 15-17 years) in Sanandaj during the academic year of 2013-2015. The study population was selected through multistage sampling method. The students filled out some questionnaires covering such data as knowledge, attitude, self-efficacy, social support (as reinforcing factors), enabling factors, and SCPBs. The data were analyzed using one-way ANOVA, independent t-test, Pearson correlation coefficient, and linear regression in SPSS software, version 21. Results: According to the results, SCPBs showed a direct correlation with attitude (r=0.175), self-efficacy (r=0.509), social support (r=0.332), and enabling factors (r=0.347). The mean SCPBs among the students was lower than moderate. The results of linear regression analysis revealed that the independent variables predicted 29.9% of SCPBs within which self-efficacy was the only significant variable (P<0.001, β=0.416). Conclusion: As the findings indicated, perceived self-efficacy was a vital factor for performing SCPBs. Therefore, perceived self -efficacy should be considered as the first priority while planning for skin cancer prevention programs for high school students.